Effects of Psychological Status on The Oxidation Parameters of Semen and Blood in Azoospermic Men - gumus, kemal; Gulum, Mehmet; Yeni, Ercan; Ciftci, Halil; Akin, Yigit; Huri, Emre; Celik, Hakim; Erel, Ozcan (Urology Journal, 2019)
Purpose: In limited number of studies performed concerning the psychological moods of female, and male with the diagnosis of infertility, data related to increased incidence of depression, and anxiety have been reported. The objective of this study is to determine whether azoospermia has any psychological effects on men, and investigate the potential effects of psychological mood on seminal, and plasma oxidative parametres. Materials and Methods: Twenty-seven patients whose two consecutive semen analyses were reported as pellet –negative azoospermia constituted the azoospermic group, and 30 healthy individuals who applied to the infertility polyclinic with normal seminal parametres comprised the normozoospermic group. Results: BECK Anxiety scores were significantly higher in the azoospermic group (P = 0.009). When compared with the normozoospermic group, higher levels of oxidative parametres, but lower levels of the antioxidative parametre were detected in the azoospermic group (P < 0.05). In the azoospermic group, a positive correlation was detected between BECK Anxiety and total oxidant status. Anxiety may increase oxidative parametres in both plasma, and seminal fluid (r = 473, p = 0.026). Conclusion: Anxiety may increase oxidative parametres in both plasma, and seminal fluid. Oxidative milieu may impair sperm quality, and affect the success rates of assisted reproductive treatments. The determination of oxidative potential in infertile men, thiol, and prolidase may be used as biomarkers.